DESAIN KOMUNIKASI VISUAL SEBAGAI MEDIA PROMOSI DI AKUN INSTAGRAM @SRAWUNGSEDUH.VOL2 - Fatara Rahmanasta'in (MEDIAKOM, 2023)
The use of social media, especially Instagram, as a promotional tool is increasingly important in various contexts such as event and product promotion. Instagram provides a powerful visual platform to effectively reach audiences. This research explores the use of visual communication design on Instagram as a promotional medium, with a case study of @srawungseduh.vol2 successfully leveraging it. The primary objective of the study is to provide insights into effective strategies and techniques in visual communication design that not only attract but also enhance user interaction. The research method employed was purposive sampling, aimed at contributing to understanding the effectiveness of visual communication design in the digital era and its utilization on social media. The findings indicate that design plays a crucial role in capturing attention and influencing audience participation. By utilizing iconic visual elements and smart color combinations, the design creates aesthetic and informative impressions. Instagram's strategy proves effective in reaching a broader audience, supported by comprehensive audience research to optimize visual content. This research deepens understanding of how visual communication design can be a key factor in successful promotion through social media platforms like Instagram.